Sistem Pencatatan Data Penggunaan Air Berbasis Smartphone Android - Heri Andrianto; Kemal Hafidzar (Maranatha University Press, 2019)
Currently, the recording of water usage is still done manually. A more practical and efficient recording system for water usage is needed. In this paper, a water meter data logger system has been designed. This system consists of a water meter device and a smartphone application. Communication between the water meter device and smartphone via a Wireless Fidelity (WiFi) connection. The water meter device uses the Wemos D1 Mini Module as a controller and flow sensor to find out the amount of water used. Data received by the smartphone from the water meter device will be processed and entered into the smartphone database (SQLite). From the test results, the water meter device can calculate water usage with an average error of 0.2957. Water usage data can be stored in a database on a smartphone. The distance of the wireless connection range between the water meter device and the smartphone is 37 meters without a barrier and 16 meters with a barrier.